2015
DOI: 10.1111/cen.12762
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D supplementation during pregnancy prevents vitamin D deficiency in the newborn: an open‐label randomized controlled trial

Abstract: Vitamin D supplementation of vitamin D deficient pregnant women prevents neonatal vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 23 publications
4
42
0
2
Order By: Relevance
“…We observed that the cord blood serum concentration of 25(OH)D was in the range of sufficient level (>75 nmol L −1 ) in both groups, and a non‐significant difference was found between groups. Consistent with our findings, an open‐label randomized controlled trial showed that maternal vitamin D supplementation (2,000–4,000‐IU cholecalciferol) among women with VDD/insufficiency from 12 to 16 weeks of gestation until delivery prevents neonatal VDD (Rodda et al, ). It is likely that placental transportal sites, notably megalin–cubilin system, are saturated with taking a certain dose of vitamin D a day (Hollis & Wagner, ).…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the cord blood serum concentration of 25(OH)D was in the range of sufficient level (>75 nmol L −1 ) in both groups, and a non‐significant difference was found between groups. Consistent with our findings, an open‐label randomized controlled trial showed that maternal vitamin D supplementation (2,000–4,000‐IU cholecalciferol) among women with VDD/insufficiency from 12 to 16 weeks of gestation until delivery prevents neonatal VDD (Rodda et al, ). It is likely that placental transportal sites, notably megalin–cubilin system, are saturated with taking a certain dose of vitamin D a day (Hollis & Wagner, ).…”
Section: Discussionsupporting
confidence: 90%
“…They concluded that vitamin D supplementation with a dose of 50,000 IU vitamin D every 2 weeks could decrease the incidence of GDM [48]. In an accordant study, Rodda et al conducted an open-label randomized controlled trial and reported the preventive effects of vitamin D supplementation in neonatal deficiency among deficient mothers [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Maternal vitamin D insufficiency from prolonged hospitalization might irreversibly affect the fetal bone metabolism, although the levels might have recovered after discharge. Recently, Rodda et al . demonstrated that supplementation of vitamin D in women with low vitamin D concentration during pregnancy increased 25(OH)D concentration in the umbilical cord blood at delivery.…”
Section: Discussionmentioning
confidence: 99%